Community Attitudes Reflect Reporting Rates and Prevalence of Animal Mistreatment - Glanville, Carmen; Ford, Jennifer; Cook, Rebecca; Coleman, Grahame J. (Frontiers in Veterinary Science, 2021)
Community attitudes towards the treatment of animals are important to understand for the development of intervention programs to prevent mistreatment. We aimed to investigate whether previously identified differences between Local Government Areas (LGAs) in the rates of animal mistreatment reporting and prevalence were reflected by differences in community attitudes. Additionally, attitudinal differences based on target species (dogs, cats, horses) and participant gender were considered. A representative telephone survey (N=1801) was conducted across six LGAs. Attitudinal themes included affection towards animals, valuing of animals, attitudes towards caring for own animals, and concern for the mistreatment of other animals. Factorial ANOVA was used to identify differences between high and low reporting LGAs, region types (regional, interface, metropolitan), and target species (cat, dog, horse). Respondents from high reporting LGAs demonstrated slightly more affection for animals F(1,1679)=19.401, p<0.001, ωp2=0.011 and stronger subjective norms F(1,999)=16.31, p<0.001, ωp2=0.015 than those from low reporting LGAs, but did not differ on the other variables. Participants in areas of high prevalence (regional areas) did not display lower levels of affection or concern for the mistreatment of animals as a whole, nor did they value animals less. However, regional differences were found for several items regarding caring for one’s own animals; two behavioural beliefs and two control beliefs. Additionally, various differences were found between the regions regarding the level of concern for mistreatment when broken down into the different species. Gender effects were also common. While the attitudinal results do reflect animal mistreatment prevalence and reporting rates, they also highlight the complexity of community attitudes. As such, interventions to prevent mistreatment must have clear targets including the audience, behaviour, and species. Targeting smaller regions and thoroughly investigating their unique perspectives, challenges, and strengths, is likely to be more effective than generic campaigns.